Mandibular intraosseous pseudocarcinomatous hyperplasia: a case report. (December 2016) - Fuchs, Andreas; Hartmann, Stefan; Ernestus, Karen; Mutzbauer, Grit; Linz, Christian; Brands, Roman; Kübler, Alexander; Müller-Richter, Urs
Abstract Background Mandibular pseudocarcinomatous hyperplasia is a rare and generally benign pathology. We report on one of these rare cases. Case presentation The case history of a 73-year-old white man stated that he had a carcinoma of the oropharynx, which was primarily treated with radiotherapy and chemotherapy 4 years prior. As a result of radiotherapy he developed an osteoradionecrosis of his mandible and a consecutive pathological fracture of his left mandibular angle. Subsequent osteosynthesis was performed with a reconstruction plate. When we first saw him, his reconstruction plate was partially exposed with intraoral and extraoral fistulation. The resected bone of his defect-bordering jaw showed the typical pathohistological findings of an intraosseous mandibular pseudocarcinomatous hyperplasia. After a first reconstruction attempt with an iliac crest graft failed, definitive reconstruction of his mandible with a microvascular anastomosed fibula graft was achieved. Conclusions Intraosseous pseudocarcinomatous hyperplasia of the mandible is a rare differential diagnosis in maxillofacial surgery. Besides other benign epithelial neoplasms, such as calcifying epithelial odontogenic tumor, squamous odontogenic tumor, or different forms of ameloblastoma, the far more frequent invasive squamous cell carcinoma needs to be excluded. A misinterpretation of pseudocarcinomatous hyperplasia as squamous cell carcinoma must be avoided because it can lead to a massive overtreatment.